Los japonesismos religioso-filosóficos en el español actual - Fernández Mata, Rafael (El Colegio de México, 2019)
Japanese loanwords relating to religion and philosophy constitute theseventh biggest semantic field –a position that they also share with Japanese loanwords related to home-furniture and clothing– of all such words used currently in Spanish (4 words out of a total of 92). In the present article an attempt is made for the first time in Spanish to offer an exhaustive description of religious and philosophical Japanese loanwords from a formal, semantic and historical perspective. The degree to which these loanwords adapt to the Spanish lexicon is also indicated.